The incremental model in software development: a structured and interactive way to deliver quality products (Research, Society and Development, 2023)
This article aims to explore the incremental model of software development, addressing its pros and cons, as well as proposing discussions about potential improvements to increase its efficiency. The incremental model is an agile and iterative methodology that enables the delivery of results in stages and in a short time, allowing clients to closely monitor project progress and make adjustments or changes if necessary. However, the model can also face challenges, such as the possibility of rework and the requirement of effective change management. At the end of the article, ask yourself if the incremental model is an adequate alternative for the current professional scenario, which requires more and more agility and dynamic project deliveries. Possible improvements that could be integrated into the model to make it even more agile to market demands will be examined. Using an approach that seeks qualitative information to validate the problem presented, it is concluded that the incremental model is an excellent option for companies that aim to deliver high quality products in a short period, provided that an efficient change management is carried out and that prevents improvements are integrated into the model according to the needs of the market.